Cytokine super-families affect adult stem cells : IL-6 and the skeletal muscle niche - Steyn, Paul (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2011.